J wave hidden among artifacts in a patient with moderate hypothermia - Aneta Małgorzata Kucharczyk-Foltyn; Dagmara Ewa Bijak (Folia Cardiologica)
The paper presents a case of 48-year-old man who was admitted to the internal ward due to moderate hypothermia. The ECG, performed upon admission, showed J wave, hidden among artifacts, caused by muscle contractions. The present case indicates that even suboptimal ECG recording may be a source of important information.